Gender specific association of ABCA1 gene R219K variant in coronary disease risk through interactions with serum triglyceride elevation in Turkish adults - Coban, Neslihan; Onat, Altan; Komurcu Bayrak, Evrim; Gulec, Cagri; Can, Gunay; Erginel Unaltuna, Nihan (Anadolu kardiyoloji dergisi : AKD, 2014)
ATP binding cassette transporter A1 (ABCA1) controls the reverse cholesterol transport. Some ABCA1 variants are correlated with serum high-density lipoprotein cholesterol (HDL-C) and other lipid concentrations. We aimed to explore the relationship of ABCA1 gene with both the lipid profile and coronary heart disease (CHD) risk. Selected 627 individuals of the Turkish Adult Risk Factor Study were genotyped for ABCA1 R219K polymorphism using PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism) method. Student's t-test, one-way ANOVA, Chi-square test, linear and logistic regression was used for statistical analysis. We demonstrated a gender-specific effect of the R219K polymorphism on plasma lipids and CHD. In men, while homozygosity of the K allele was associated with increased plasma low-density lipoprotein cholesterol (LDL-C) (p<0.05) and total cholesterol concentrations (p<0.05), carriage of this allele was associated with higher HDL-C concentrations (p<0.05) after adjustment for associated risk factors, but not with CHD. In women, however, without being related to HDL-C levels, each 219K allele was associated with 10% higher triglycerides (TG) concentrations (p<0.05). R219K heterozygosity in women independently doubled (95% CI 1.00; 3.80) the odds ratio for CHD risk in regression models, after adjustment for several variables. Interaction of TG elevation (>140 mg/dL) with CHD was demonstrated in female 219RK genotype carriers. R219 allele of the ABCA1 gene independently confers CHD risk in heterozygote Turkish women, not via reduced HDL-C, but interacting with elevated TG expressed by the 219K allele, but not in men.